(untitled) (Revista Venezolana de Salud Pública, 2019)
This essay lays out some thoughts regarding medical practice in Venezuela, according to what expert doctors( UCV, UCLA) and young specialist doctors (UCLA) have expressed in the 21st century Socialist Venezuela, in Universidad Centroccidental Lisandro Alvarado (UCLA. Venezuela). The interest focused on interpreting with a critical view the meanings of the medical discourse regarding medical practice. It took in its core the qualitative paradigm in the critical interpreting method, I worked with critical hermeneutics by Gadamer y Habermas, the critical analysis of speech described by Teum Van Dijk. The following findings emerged from the research: While expert doctors focused their attention on the “ought-to-be” of the medical practice, characteristics, challenges and contradictions of said practice in the Socialist Venezuela of the 21st century, the young doctors focused their attention on the theoretical disparity of the training received in the actual work field, the exercise of power, violence in health care centers, their aspirations and obstacles for the development of a suitable and equitable medical practice, adequate to the needs of the population assisted by the healthcare services. The concerns set out was presented as a reflexive essay, give an account of the findings while researching in the 2015/16 period in Venezuela. The different experiences of social players, inquired authors and the author of the essay enable to clearly reveal co-existent and dynamic points of view about Medical Practice in Venezuela and the change outlooks that might be useful for the reconstruction of the Healthcare Service so needed by the Venezuelan people.